THE ROLE OF LEAF WATER CLOVER (Marsilia crenata) SQUEEZE TOWARDS ESTROGEN BLOOD LEVEL AND UTERINE HISTOLOGY IN RATS (Rattus norvegicus) - Pratiwi Trisunuwati (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2016)
Water clover (Marsilea crenata) is contained with isoflavones, shown to mimic the role of the female hormone estrogen. Isoflavones binding to estrogen receptors that produce beneficial effects. However, research on the optimal dose of water clover use is still not much studied. The purpose of this study was to determine the effects of leaf squeeze water clover towards estrogen and how affect the histology of uterine. This study used 30 female Wistar Rats (Ratus norvegicus) divided into six groups. P1 as a negative control group, P2 as a positive control group. P4, P5 and P6 were given squeeze water cloverleaf concentrations given as follow (6.25%, 12.5%, 25%, 50%). The results was analized with one way ANOVA showed significant (p< 0.05) between groups, among group P3, P4, P5 and P6 increase the blood estrogen mostly higher than the negative control (P1) and a positive control (P2). Histological features of the uterus in the positive control group showed endometrial lining thicker than the negative control group. Histology of the uterus in the treatment group P4, P5 and P6 are also seen endometrium thickening as in group P3. This research has proved that water clover extract consumption show a promising supporting phytoestrogen hormone theraphy in the future both in animal and human. However there was needed a much futher research in order to found a proper dose for as a prospective pytotherapy. Keyword: Water Clover (Marsilia crenata), estrogen, uterine histology